2011
DOI: 10.4103/1119-3077.86774
|View full text |Cite
|
Sign up to set email alerts
|

The state of occupational radiation protection and monitoring in public and private X-ray facilities in Edo state, Nigeria

Abstract: There are inadequate radiation protection and monitoring practices in most of the functional X-ray facilities in Edo state with only five (62.5%) of the private and two (20%) of the public X-ray units monitored. There is poor adherence to the advice of the medical physicists due to the cost implications of the implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The knowledge, awareness and practice of radiographers in X-ray diagnostic centers should be taken seriously in X-ray diagnostic centers. In addition, the use of personal protecting equipment is efficient to avoid health issues that may arise from radiation dose exposure [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge, awareness and practice of radiographers in X-ray diagnostic centers should be taken seriously in X-ray diagnostic centers. In addition, the use of personal protecting equipment is efficient to avoid health issues that may arise from radiation dose exposure [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…The essence of dose monitoring for all staff is also to assist in picking up radiation leakages beyond the controlled area hence ensuring safety for staff, patients and their accompanying relations. Many studies have shown that the attitude and practice of radiation monitoring is not commensurate with the good knowledge possessed by staff of radiation departments [7,8]. The reverse is true of the findings in a study by Mojiri et al [9] which reported high awareness of the necessity of application of monitoring device among the participants.…”
Section: Discussionmentioning
confidence: 98%
“…Elsewhere, especially in Nigeria, even if most of radiologist technician have good knowledge of radioprotection measures, there are inadequate radiation protection and monitoring practices in most of the functional X-ray facilities. There is poor adherence to the advice of the medical physicists due to the cost implications of the implementation (Qutbi et al, 2021;Eze et al, 2011). In Benin, the status of the implementation of radiation protection measures in medical imaging (MI) units is little known, and reports of internal or external monitoring of compliance with standard radiation protection processes are rare.…”
Section: Introductionmentioning
confidence: 99%